Managing investment risks of institutional private equity investors: The challenge of illiquidity - Christoph Kaserer; Niklas Wagner; Ann-Kristin Achleitner (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2003)
Since private equity investments are not publicly traded, a key issue in measuring investment risks of institutional private equity investors arises from a careful measurement of investment returns in the first place. Prices of private equity investments are typically observed at low frequency and are determined by transactions under low liquidity. This contribution highlights useful approaches to the problem of return measurement under conditions of illiquidity. Then, specific risk management issues, including asset allocation issues, are discussed.
Keywords: G1; G2; 330; private equity; risk/return measurement; net asset values; cash flows; illiquidity; stale pricing; risk management; asset allocation